Differentiation Methods in Islamic Education Learning - Ariatman, Roby; Supardi, Supardi; Lubna, Lubna (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2024)
This study aims to analyze the differentiation method in learning Islamic religious education. This research uses a descriptive qualitative approach. Data were collected through classroom observations and interviews with Islamic religious education teachers at SDN 1 Montong Baan, as well as documentation to collect data related to the study in this research. The result of this research is that the differentiation method in learning Islamic religious education has three components. The content component includes the material of al-Qur'an hadith, fiqh, akidah akhlak, Islamic history. The process component includes the suitability of the method with the needs of students' learning styles, namely visual, auditory, and kinesthetic learning styles. The product component includes students' freedom in expressing the material obtained in the learning process using the differentiation method, such as presenting the material that has been obtained through individuals and groups and making essays.